The Impact of Disclosure of Segment Information on The Appropriateness of Financial Reporting Information - Zaito Awla Abubakr; Rezan Salahaddin Azzat (QALAAI ZANIST JOURNAL, 2024)
The research aims to shed light on the study and testing of the impact of segment information disclosure on the appropriateness of financial reporting information. To achieve the goal of the research, the inductive approach was relied upon by preparing a questionnaire for this research, which was distributed to a random sample among the community of auditors and accounting academics in universities and institutes in the city of Erbil, who numbered (83) individuals, whose results were then analyzed by the statistical program. (SPSS). The research reached a set of conclusions, the most prominent of which is the existence of a statistically significant effect of the disclosure of sectoral information on the appropriateness of financial reporting information. In the end, the research presented some recommendations, the most important of which is the need for companies operating in Iraq in general and the Kurdistan Region in particular to commit to disclosing sectoral information in preparing financial reports, especially companies that enjoy different sectors due to their importance due to their characteristics that make accounting information appropriate and useful for decision-making by Users of these reports in order to understand the complexity of large companies and diversified activities, and to evaluate and understand the performance of these companies more accurately than the aggregate information